Effective Use of Modern Technologies in Education Lessons is an Important Factor in the Education of a Perfect Person (Journal of Pedagogical Inventions and Practices, 2023)
In this article, the positive features of instilling educational lessons organized by pedagogues into the minds of students through modern methods and technologies, as well as their place in the development of society, are discussed.